Development of a CO2 Cooling Test Facility from the Vertex Locator Thermal Control System - Lunt, Stuart (Department of Electrical Engineering, 2025)
The Vertex Locator Thermal Control System (VTCS) was a mechanically pumped, evaporative CO2 cooling system developed for silicon strip detectors in the Large Hadron Collider beauty (LHCb) experiment at the European Organisation for Nuclear Physics (CERN). This type of cooling has become increasingly common in high-energy physics experiments, making their design and testing increasingly more important. The Detector Technologies (DT) group chose to reuse the hard ware from the VTCS after it was retired and convert it into a test facility for future detectors. This dissertation describes the analysis and redesign of the electrical, fluid and control systems which was undertaken to optimise the design for its new role and to bring it into line with current standards in the field. Alongside the hardware design, a model of the system was developed in Simulink, enabling the performance to be simulated with different hardware configurations and to assess its suitability for different applications. Delays in travel and procurement caused by the COVID-19 pandemic did not allow final construction and commissioning to be fully completed by the end of the project.